Post-vaccination T cell immunity to omicron - Jacobsen, Henning; Cobos Jiménez, Viviana; Sitaras, Ioannis; Bar-Zeev, Naor; Čičin-Šain, Luka; Higdon, Melissa M.; Deloria-Knoll, Maria (Frontiers in Immunology, 2022)
In late 2021, the omicron variant of SARS Coronavirus 2 (SARS-CoV-2) emerged and replaced the previously dominant delta strain. Effectiveness of COVID-19 vaccines against omicron has been challenging to estimate in clinical studies or is not available for all vaccines or populations of interest. T cell function can be predictive of vaccine longevity and effectiveness against disease, likely in a more robust way than antibody neutralization. In this mini review, we summarize the evidence on T cell immunity against omicron including effects of boosters, homologous versus heterologous regimens, hybrid immunity, memory responses and vaccine product. Overall, T cell reactivity in post-vaccine specimens is largely preserved against omicron, indicating that vaccines utilizing the parental antigen continue to be protective against disease caused by the omicron variant.